Urinary Microbiota of Healthy Prepubescent Girls and Boys—A Pilot Study - Yulia L. Naboka; Mikhail I. Kogan; Johannes M. Mayr; Irina A. Gudima; Elizaveta M. Koliva; Violetta M. Kotieva; Marina L. Chernytskaya; Vladimir V. Sizonov (Children)
Background: The urinary microbiota of healthy children has rarely been studied, and potential differences between boys and girls have not been addressed. Thus, this study aimed to compare the urinary microbiota of healthy prepubescent girls and boys. Methods: We included healthy children aged between 4 and 10 years who were free of functional or organic urinary tract diseases and had no history of urinary tract infection. We collected the mean portion of morning urine during natural micturition and determined aerobic and anaerobic microbiota using HiCrome™ chromogenic growth media. We identified microorganisms on the basis of morphotinctural properties and analyzed α- and β-diversity of microorganisms isolated from the urine of boys and girls. Results: Mean age of the children was 6.1 ± 3.2 years. In general, four-component (28.1%) as well as two-component (15.6%), three-component (15.6%), and six-component (12.5%) combinations of microorganisms prevailed in the urine of children. The urine of boys exhibited four-component combinations significantly more often than that of girls (p ˂ 0.05), while the urine of girls contained seven-component microbial combinations significantly more often than that of boys (p ˂ 0.05). Comparison of multicomponent combinations of microorganisms in boys and girls revealed an overrepresentation of Enterococcus spp. in girls (p < 0.05). Furthermore, there was a trend towards higher microbial α-diversity in the urine of girls, but the difference between girls and boys was not significant. Conclusions: The urine of healthy prepubescent children contained various aerobic–anaerobic combinations of microorganisms. Their diversity in the urine of girls and boys did not differ significantly. However, the level of α-diversity of microorganisms was higher in girls than in boys. We noted differences in the prevalence of certain taxa of microorganisms in the urine of boys and girls. Our study showed a close functional relationship between aerobic and anaerobic microorganisms detected in the urine of children in more than half of the cases.